IMPLEMENTASI BIMBINGAN DAN KONSELING UNTUK MENINGKATKAN SELF ESTEEM PASIEN PENYAKIT TERMINAL DI KELOMPOK DUKUNGAN SEBAYA (KDS) RSUP DR. KARIADI SEMARANG - Hidayanti, Ema (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2018)
HIV / AIDS patients experience complex problems both physically, psychologically, socially, and spiritually. Psychosocial problems experienced include depression, anxiety, despair, and worry, and affect the destruction of social life such as isolating themselves and getting stigmatized. These various problems make HIV / AIDS patients feel useless and worthless. In dealing with psychological problems such as low self-esteem, HIV / AIDS patients desperately need social support from both partners, parents, children, friends, counselors and health teams. Unfortunately during this time the expected social support, rarely HIV / AIDS patients were found, including from their own families. To facilitate these needs, hospitals that become a reference center for HIV / AIDS patients form Peer Support Groups (PSG). PSG activities include group guidance and peer counseling for HIV / AIDS patients. These activities provide opportunities for HIV / AIDS patients to increase knowledge about their illness, exchange experiences with each other, even help each other solve problems. The various positive benefits of peer support groups in turn can increase the self-esteem of HIV / AIDS patients. ****Pasien HIV/AIDS mengalami problem yang kompleks baik fisik, psikologis, sosial, dan spiritual. Problem psikososial yang dialami antara lain depresi, cemas, putus asa, dan khawatir, serta berpengaruh pada rusaknya kehidupan sosial seperti mengisolasikan diri dan mendapat stigmatisasi. Berbagai masalah tersebut membuat ODHA merasa tidak berguna dan tidak berharga. Dalam menghadapi problem psikologis seperti rendahnya harga diri, ODHA sangat membutuhkan dukungan sosial baik dari pasangan, orang tua, anak, teman, konselor dan tim kesehatan. Sayangnya selama ini dukungan sosial yang diharapkan tersebut, jarang ODHA didapatkan termasuk dari keluarganya sendiri. Untuk memfasilitasi kebutuhan tersebut, rumah sakit yang menjadi pusat rujukan bagi ODHA membentuk Kelompok Dukungan Sebaya (KDS). Kegiatan KDS diantaranya bimbingan kelompok dan konseling sebaya bagi ODHA. Kegiatan tersebut memberikan peluang bagi ODHA untuk menambah pengetahuan tentang sakitnya, bertukar pengalaman dengan sesamanya, bahkan saling membantu memecahkan masalah. Berbagai manfaat positif KDS tersebut pada gilirannya mampu meningkatkan harga diri ODHA.